Antioxidant profile of commercial oenological tannins determined by multiple chemical assays. (3rd January 2014) - Magalhães, L. M.; Ramos, I. I.; Reis, S.; Segundo, M. A.
Abstract Background and Aims The addition of oenological tannins during winemaking is a longstanding technological practice. To assist such a practice, knowledge of their antioxidant properties is an asset for understanding their role in redox processes occurring in wine. Hence, the aim of this work was to assess the antioxidant profile of oenological tannins from several botanical sources, which are usually applied at different winemaking steps. Methods and Results Several antioxidant assays, including the ability to reduce copper(II) assay (CUPRAC), the scavenging capacity against 2, 2′‐azinobis‐(3‐ethylbenzothiazoline‐6‐sulfonate) (ABTS) and 2, 2‐diphenyl‐1‐picrylhydrazyl radicals (DPPH), and the peroxyl radical scavenging capacity (oxygen radical absorbance capacity assay, ORAC) were applied. The concentration of phenolic substances and the ability to chelate iron(II) (ICA) were also determined. A significant correlation was obtained between the concentration of phenolic substances and the copper(II) reducing antioxidant capacity (R = 0.89), and the 2, 2′‐azinobis‐(3‐ethylbenzothiazoline‐6‐sulfonate) (R = 0.86) and 2, 2‐diphenyl‐1‐picrylhydrazyl (R = 0.86) assays. No such correlation was observed (R = 0.15) with the oxygen radical absorbance capacity assay. Conclusions The highest radical scavenging capacity was attained for oenological tannins composed of gallotannins, while those containing ellagic acid were able to chelate iron(II) strongly, preventing the oxidative damage mediated by Fenton‐based reactions. Condensed tannins demonstrated a significant ability to scavenge peroxyl radicals, which represents a powerful antioxidant mechanism to prevent lipid peroxidation. Significance of the Study The chemical antioxidant profile of oenological tannins displayed in radar charts provides valuable information for winemakers and manufacturers of oenological tannins.